2020
DOI: 10.31067/0.2019.138
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Travmayı Azaltmaya Yönelik Alternatif Yöntemler

Abstract: Perineal travma nedenlerinden biri olan epizyotomi, dünya çapında 20. yüzyıl boyunca önemli derecede artış gösteren obstetrik cerrahi uygulamalardan biridir. Amerika Jinekoloji ve Obstetrik Birliği (2016) spontan vajinal doğumlarda epizyotominin rutin olarak uygulanmasını önermemekte ve epizyotomi uygulamasına fetüsün hızlıca doğurtulması gereken durumlarda, operatif vajinal doğumlarda ve omuz distozisi durumlarında başvurulması gerektiğini belirtmektedir. Yapılan güncel çalışmalarda dünyada epizyotomi sıklığı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…However, the results of this study reported no difference between patients’ pain levels based on gender. Most of the studies in the literature related to pain during IM injection which compared pain levels according to IM injection sites (Güneş et al, 2013; Kara, 2013; Kilic et al, 2014; Rodríguez et al, 2017; Tuğrul & Khorshıd, 2014; Yilmaz et al, 2016) and many of these studies did not compare pain according to gender. Results similar to the findings of the present study were obtained in the limited number of comparison studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of this study reported no difference between patients’ pain levels based on gender. Most of the studies in the literature related to pain during IM injection which compared pain levels according to IM injection sites (Güneş et al, 2013; Kara, 2013; Kilic et al, 2014; Rodríguez et al, 2017; Tuğrul & Khorshıd, 2014; Yilmaz et al, 2016) and many of these studies did not compare pain according to gender. Results similar to the findings of the present study were obtained in the limited number of comparison studies.…”
Section: Discussionmentioning
confidence: 99%
“…IM injection, one of the invasive procedures administered to patients in the hospital, is one of the most painful applications. It is reported that the pain associated with IM injection is due to the mechanical trauma caused by the needle insertion and the sudden pressure created when the substance is administered intramuscularly (Kara, 2013). Previous studies determined that IM injections that are administered without aspiration are less painful and the injection time is shorter (Girish & Ravi, 2014; Ipp et al, 2007; Sisson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Üç yaşın altındaki çocuklarda invaziv girişimlerden kaynaklı semptomların azaltılmasında dikkati başka yöne çekme yönteminin etkili olması nedeniyle öncelikli olarak önermektedir (Taddio ve ark., 2015) (Özveren, 2011;Srouji ve ark., 2010;Uğurlu 2017). IM enjeksiyon uygulamaları ile ilgili yapılan literatür taramasında shotblocker ve soğuk uygulama ile ilgili çalışmaların sıkça yapıldığına rastlanmıştır (Çelik ve Khorshid, 2012;Hasanpour ve ark., 2006;Kara, 2013). SC enjeksiyon uygulamasına ilişkin ise enjeksiyondan kaynaklı yaşanan ağrı, ekimoz ve hematom gibi semptomların azaltmasına yönelik yapılan birçok çalışmanın olduğu görülmektedir (Küçükgüçlü ve Okumuş, 2010;Ordu ve Oksay Şahin, 2020).…”
Section: Farmakolojik Yöntemlerle Birlikte Uygulananunclassified
“…Episiotomy leads to such complications as postpartum perineal pain, dyspareunia, pain and infection in the perineal region, risk of contamination with urine and stool, pain and prolongation of the healing process, the relationship between mother and infant, and postpartum sexual life being affected adversely (6,7). Furthermore, the repair of episiotomy prevents skin-toskin baby contact and early breastfeeding in the first half hour, which is highlighted as the golden time according to SOGC (8,9). Therefore, it is recommended to limit the routine use of episiotomy to reduce non-spontaneous perineal traumas.…”
Section: Introductionmentioning
confidence: 99%